Otok pred Izolo - Steinman, Franci (Urbani izziv, 2002)
Maritime construction in front of Izola restitutes an enriched former state. The island is positioned in a place where there are no legal regimes enforced by the state or local community. Legal regimes that determine the exploatationof water rights and limitations (management, exploatation, use) can actually limit all, therefore their synthesis has to be the starting pointfor analysing the harmony of present uses and for planning future uses ofthe sea and coastal area. For example the aquatorij of the shell fish mariculture positioned in the Strunjan Bay without adequate analysis of the prevailing conditions is causing conflicts of uses, unacceptable limiting of general use of the sea and prohibitive limitations in neighbouring areas. The analysis done for the island in front of Izola shows that there are no such consequences. Only uses in the public interest were proposed, since when assessing suitability first public and then common interests where considered,possible specific (e.g. entrepreneurial) uses were permited only ifthe afore mentioned weren't obstructed. Thus integral management of the coastal area was enabled, with respect to functional ties between the land andsea.
Keywords: coast; ecology; ekologija; Izola; morje; obala; otoki; prostorsko planiranje; raba tal; sea; slovensko primorje; spatial planning; vodno gospodarstvo